PENGARUH E-COMMERCE DAN SISTEM INFORMASI AKUNTANSI TERHADAP KINERJA UMKM TERHADAP KINERJA UMKM SEKTOR INDUSTRI - Oniela Ramadhana Ulyasari; Duwi Agustina; Rulyanti Susi Wardhani; Athur Waga Ilhamsyah (LPPM Institut Pendidikan Nusantara Global, 2023)
This research aims to determine whether e-commerce and accounting information systems affect the performance of SMEs. The type of research used in this research is research with a quantitative approach. The sampling method used was cluster random sampling technique with a total of 350 respondents in Sungailiat District. The analysis technique used is descriptive statistics and multiple linear regression analysis. The results show that e-commerce and accounting information systems have a positive and significant impact on the performance of MSMEs in the industrial sector in Sungailiat District.